A Study of Temperature‐Dependent Photoluminescence from As‐Deposited and Heavy‐Ion‐Irradiated Plasma‐Enhanced Chemical Vapor Deposition‐Grown Si‐Rich a‐SiNx:H Thin Films. Issue 5 (17th December 2019) - Gupta, Harsh; Plantevin, Olivier; Bommali, Ravi K.; Ghosh, Santanu; Srivastava, Pankaj
Abstract : Temperature‐dependent photoluminescence (PL) measurements in the range of 10–300 K are carried out on silicon‐rich hydrogenated silicon nitride films deposited by plasma‐enhanced chemical vapor deposition. The in situ formation of Si quantum dots (QDs) with an average size of 3.5 nm is observed. The composition of thin films is estimated by Rutherford backscattering and ellipsometry. Broad PL spectra from thin films are decomposed into contributions from Si QDs, N dangling bonds (DBs), and Si DBs ( K ‐centers). At a low temperature, a strong PL can be observed, its quenching with increase in temperature is explained by the thermal activation of nonradiative decay mechanisms. Further, temperature‐dependent PL for swift heavy‐ion‐irradiated films shows similar quenching with increase in temperature. However, the effect of irradiation on the luminescence mechanisms of a ‐SiN x :H is revealed at low temperatures (<120 K) only, whereby a relatively narrow peak around 2.0 eV emerges. These results clearly show the role of radiative defects in the luminescence from Si‐rich silicon nitride. Abstract : Temperature‐dependent photoluminescence measurements are carried out on as‐deposited and swift heavy‐ion‐irradiated a ‐SiN x :H films. At a low temperature, a strong photoluminescence for both as‐deposited and irradiated films is attributed to defects and Si quantum dots, which quenches with increase in temperature due to the activation of nonradiative recombination. However, the effect of irradiation on luminescence mechanisms of a ‐SiN x :H is revealed at low temperatures (<120 K).